DESIGN OF A PROTOCOL FOR TENSILE TESTING OF LOW ALLOY STEEL REBARS FOR STEEL REBARS FOR CONCRETE REINFORCEMENT UNDER NTC 2289 AND NTC 3353. CONCRETE REINFORCEMENT, UNDER NTC 2289 AND NTC 3353 STANDARDS. - Largo Arboleda, Breyner Stevens
A tensile test for a metallicmaterial allows to performance a mechanicalcharacterization of the material. An axial loadis applied to a test item.As the load is applied, deformationmeasurements are taken, which are usedto construct the stress-strain curve, up tothe point of maximum load or maximumresistance.With the construction of the graph,characteristics of the material such as yieldstress, maximum stress, and deformation afterfracture is obtained.This data is very important for thevalidation and evaluation of the qualityof the steels to be used in sectors such ascorrugated steel, which is a material of greatinterest in the construction industry, since itis used in concrete reinforcement works instructures with seismic resistant design..However, when performing tensiletests there are unknowns with respect tohow the results can be affected by thespeed of the test in determining your resultscan be affected by the speed of the test indetermining its mechanical characteristics.Although there are internationaltechnical standards for the execution of tensiletests that provide adequate methods andranges for the selection of the test speed,there are international technical standards forthe execution of tensile tests. the final choiceof this is left to the analyst to decide on whichis the most appropriate, however, when it isdesired to compare results between differentlaboratories for the same or similar items,the choice of a velocity method and a givenvelocity value influences the comparability ofthe results.This paper presents the design ofa tensile test protocol for rebars used ininfrastructure, based on NTC 2289 used ininfrastructure, based on the standards NTC2289 CORRUGATED AND SMOOTHBARS OF LOW ALLOY STEEL FORCONCRETE REINFORCEMENT andNTC 3353 SIDERURGY.LOW-ALLOY STEEL SLABS FORCONCRETE REINFORCEMENT and NTC3353 SIDERURGY. DEFINITIONS ANDMETHODS FOR MECHANICAL TESTINGOF STEEL PRODUCTS.The test protocol consists of theminimum requirements that a SENAthe laboratory must have in order to carryout an intercomparison exercise, this isall guaranteed by a third-party entityknown as the Colombian AccreditationBody (ONAC, Organismo de Acreditaciónde Colombia) which is, again, the onein charge to perform the tensile tests.In addition to the administrativerequirements, the requirements that mustbe met to carry out the tests are described,with the requirements that must be met toperform the tests, based on the operatingthe capacity of the universal testing machineof each center, the length of the minimumthe length that must be used in the rebars isdefined, and a series of speeds are proposedaccording to the series of speeds areproposed according to the requirementsdescribed in the NTC 3353 standard innumeral 8.4 and the diameter of the rebarsto be used.